Feeding raw soybeans to finishing cattle - Marston, T.T.; Kreikemeier, K.K.; Gleghorn, J.F.; Huck, G.L.; Wistuba, T.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two finishing trials were performed to determine if raw soybeans could be incorporated into diets to partially replace soybean meal and beef tallow. Our data indicated that no sacrifices in animal performance, feed efficiency, and carcass quality will occur if cattle feeders replace soybean meal and tallow with raw dryrolled soybeans. The feeding value of raw soybeans is equal to .8 times the value of 44% CP soybean meal plus .2 times the value of fancy bleachable tallow. Raw soybeans contain the enzyme, urease, which converts urea to ammonia. Therefore, caution should be used in mixing raw soybeans with urea-containing diets.
Keywords: Beef; Soybean; Protein; Fat; Finishing cattle